Robot‐assisted partial cystectomy: perioperative outcomes and early oncological efficacy. (15th June 2016) - Golombos, David M.; O'Malley, Padraic; Lewicki, Patrick; Stone, Benjamin V.; Scherr, Douglas S.
Abstract : Objective: To report on patients undergoing robot‐assisted partial cystectomy (RAPC), focusing on perioperative outcomes over a range of clinical, anatomical and pathological variables, as well as the overall oncological efficacy of this approach. Patients and Methods: We retrospectively reviewed all patients who underwent RAPC by a single surgeon between 2005 and 2015. We identified 29 patients who underwent surgery for definitive management of a primary bladder tumour. Clinicopathological data and perioperative variables were recorded. Continuous variables were compared using the Student's t ‐test. Prediction of perioperative outcomes for those undergoing RAPC for intra‐diverticular neoplasms was done using univariate logistic regression. Survival was estimated using the Kaplan–Meier method. Results: The median (interquartile range) patient age was 75 (65–81) years, 18 patients (62.1%) had an American Society of Anesthesiologists classification of ≥3, and 10 patients (34.5%) had a history of prior abdominal surgery. The median estimated blood loss (EBL) was 50 mL and the median length of stay (LOS) was 1 day. Two patients (6.9%) had a perioperative complication and five (17.9%) a post‐discharge complication at ≤90 days, all of which were minor. The positive surgical margin rate was 3.6% and in those with muscle‐invasive disease a median of 12 lymph nodes were removed. Neither the size of diverticulum nor the need for ureteric re‐implantation was predictive of LOS, EBL, or complication ( P > 0.05). We did not encounter any wound, port site, or unusual recurrence patterns to suggest the technical factors of a robotic approach influenced oncological outcomes. The 5‐year overall and recurrence‐free survival rates were 79% and 68%, respectively. Conclusion: RAPC confers the ability to achieve favourable outcomes with low morbidity and reduced hospital stays. Oncological efficacy compares favourably with the published literature. For experienced surgeons, this may represent the optimal surgical approach for organ‐preserving bladder surgery.